PERILAKU PEMBELIAN IMPULSIF MAHASISWA DI DAERAH ISTIMEWA YOGYAKARTA - Ascasaputra Aditya; Kiki Yulia Pramestya; Winda Puji Lestari; Mohammad Fauzan Irawan (Unib Press Universitas Bengkulu, 2020)
This study aims to analyze the level of impulsive buying based on differences in age, gender, and pocket money as well as the types of products purchased impulsively. This research is a form of quantitative research with a survey method. The sample collection technique used random sampling with 158 respondents participating. The analytical tools used are the analysis of the difference test t test, and One-Way ANOVA. The results in this study were there were no differences in impulsive buying in the age group and gender. Meanwhile, pocket money has proven to be different. Buferroni's Post Hoc Test results showed that the group of Rp1,000,000 - Rp2,000,000 with groups ? Rp2,000,001 had differences, but this difference proved that the low pocket money group was more impulsive than the higher pocket money group. The types of products that are bought impulsively are food, drinks, clothes, and toiletries.Keyword: Age; Gender;Impulsive Buying; Pocket Money